Direct N‐Alkylation/Fluoroalkylation of Amines Using Carboxylic Acids via Transition‐Metal‐Free Catalysis. Issue 19 (18th August 2020) - Lu, Chunlei; Qiu, Zetian; Xuan, Maojie; Huang, Yan; Lou, Yongjia; Zhu, Yiling; Shen, Hao; Lin, Bo‐Lin
Abstract: A scalable protocol of direct N ‐mono/di‐alkyl/fluoroalkylation of primary/secondary amines has been constructed with various carboxylic acids as coupling agents under the catalysis of a simple air‐tolerant inorganic salt, K3 PO4 . Advantageous features include 100 examples, 10 drugs and drug‐like amines, fluorinated complex tertiary amines, gram‐scale synthesis and isotope‐labelling amine, thus demonstrating the potential applicability in industry of this methodology. The involvement of relatively less reactive silicon‐hydride compared with the traditional reactive metal‐hydride or boron‐hydride species required to reduce the amide intermediates presumably contributes to the remarkable functional group compatibility. Abstract :